Os entraves para o surgimento da eficácia coletiva: um estudo de casos em um aglomerado de Belo Horizonte - Wilson Jose Antonio da Cruz (2010)
Crime is a phenomenon that afflicts societies around the world. Regardless of how you present yourself, which are many, is a problem with which all governments have to deal with. Crime is presented in several facets, but we are dealing, in this work, with crimes associated with gangs of drug traffickers in a cluster of Belo Horizonte. Recently another variable has been added to the approach of social crime in the suburbs. Thus, the "properties of community structures" emerge as another dimension in which the crime can be analyzed. What question is "which community characteristics are associated with high rates of crime and violence." In this sense, from a theoretical major, human ecology, (and other models connected to it) reviewed a number of slums in Belo Horizonte, peculiar in the coexistence of high rates of crimes against persons and a high degree of social cohesion among residents. Our intention in the present paper is to discuss coexistence and point to a possible description and interpretation. To this end, we are guided by the following question: Why are the communities of Sierra Particleboard are cohesive to claim goods and services, but are not able to, from this cohesion, implement a collective goal to get rid of gang activities? Why does cohesion becomes effective social control of behavior of young people?